Influence of GIDI organic fertilizer on the yield of corn - Samsia A. Ibrahim (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose: GIDI organic fertilizer or water hyacinth is an aquatic plant, an excellent depollutant, and is helpful for food production as compost and regeneration of degraded soil. Maintaining its fertility and maintaining the ecological balance of the environment. The study aimed to evaluate the influence of different rates of GIDI organic fertilizer on the yield response of corn under Rebuken, Sultan Kudarat, and Maguindanao conditions from October 2017 to January 2018.